Transport Critical Current Density of (Bi1.6Pb0.4)Sr2Ca2Cu3O10 Ceramic Superconductor with Different Nanosized Co3O4 Addition - Nur Jannah Azman; Huda Abdullah; Roslan Abd-Shukor (Advances in Condensed Matter Physics)
The effect of different nanosized Co3O4 (10, 30, and 50 nm) addition on the Bi1.6Pb0.4Sr2Ca2Cu3O10(Co3O4)x superconductor with x=0–0.05 wt.% has been investigated using X-ray diffraction method, scanning electron microscopy, transition temperature, and critical current density Jc measurements. The samples were prepared by the conventional solid-state reaction method. Samples with x=0.01 wt.% Co3O4 (10 nm) showed the highest Tc-zero at 102 K. The highest Jc was observed in the x=0.03 wt.% Co3O4 (10 nm) and x=0.02 wt.% Co3O4 (30 nm) samples. At 77 K, Jc of the 10 nm and 30 nm Co3O4 added samples was 6 and 13 times larger than the nonadded samples, respectively. Small addition of Co3O4 nanoparticles in the Bi1.6Pb0.4Sr2Ca2Cu3O10 (Bi-2223) samples enhanced the critical current density and the phase formation. The larger Co3O4 nanoparticle (50 nm) had a greater degradation affect on superconductivity of the Bi-2223 phase.